(untitled) (LEARNing Landscapes, 2009)
In this interview with Anne Haas Dyson she discusses literacy, examining the connection between language, culture, and the positive impact of play. Anne speaks about the importance of incorporating literacy into the everyday life of children, and encouraging creativity and peer collaboration in the home as well as in classrooms. She stresses that children’s literacy skills must be assessed within context, taking into consideration the child’s perspective and the resources available. She emphasizes the individuality of every child’s learning experience and the right for children to progress at their own speed.